An improved distance vector-Hop localization algorithm based on coordinate correction - Xing Wang; Yunfeng Nie (International Journal of Distributed Sensor Networks)
In order to improve the localization accuracy of distance vector-Hop algorithm under the random topology network scenarios, a novel algorithm named coordinates correction-distance vector-Hop is proposed. Coordinates correction-distance vector-Hop defines the pseudo-range error factor to improve the accuracy of average hop distance. In order to improve the localization accuracy, the unknown node uses distances to part of anchor nodes to locate. Furthermore, anchor nodes are treated as unknown when obtaining their coordinate correction values which are used to correct the localization results of unknown nodes. The simulation results show that each step of coordinates correction-distance vector-Hop can increase the localization accuracy effectively; coordinates correction-distance vector-Hop is better than the traditional distance vector-Hop and some existing improved algorithms both in localization accuracy and in localization stability.